Efektifitas Pelaksanan Program CSR PT Tirta Bahagia - Anggara Prihardana (University of Darussalam Gontor, 2015)
CSR first appeared in official discourse since the presence of academic writings of Howard Bowen, entitled Social Responsibility of Businessmen raised in 1953. CSR in the meaning of Bowen refers to the obligation of business to make and implement policies, decisions, and actions that follow the norms in a society. In the implementation of the program of corporate social responsibility (CSR), PT Tirta Bahagia has a lot of activities in the field of education, the environment or health. In carrying out these activities there are several stages performed i.e. ranging from planning, implementation, and evaluation. In this discussion that became the focus of research is on the development of the well absorption done by the company in the village which is also the location of the factory. PT Tirta Bahagia starting the planning stages are not based on the order in which they should be, i.e. starts with vision and mission would formulate but positioning the provision of funds (budget) being the first with reason a very limited source of funding, causing the program to be run CSR activities should be adapted to the existing funds.